2022
DOI: 10.3389/fimmu.2022.1032819
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the molecular mechanism of hepatitis virus inducing hepatocellular carcinoma by microarray data and immune infiltrates analysis

Abstract: The number of new cases of hepatocellular carcinoma (HCC) worldwide reached 910,000, ranking the sixth, 80% HCC is associated with viruses, so exploring the molecular mechanism of viral carcinogenicity is imperative. The study showed that both HBV and HCV associated HCC and non-viral HCC have the same molecular phenotype (low gene expression and inhibition of immune pathways), but in the tumor immune micro-environment, there is excessive M2-type macrophage polarization in virus-associated hepatocellular carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…An understanding of such implied molecular mechanisms has already started. Novel molecules that are carcinogenic to hepatitis viruses and activate the PI3K-Akt-mTOR pathway have been identified ( 19 ). These include five hub genes, POLR2A, POLR2B, RPL5, RPS6, and RPL23A, add to M2-type macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of such implied molecular mechanisms has already started. Novel molecules that are carcinogenic to hepatitis viruses and activate the PI3K-Akt-mTOR pathway have been identified ( 19 ). These include five hub genes, POLR2A, POLR2B, RPL5, RPS6, and RPL23A, add to M2-type macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the immune landscape and identifying the distinct immune cell compositions and specific immunomodulatory targets within the tumor microenvironment is pivotal in guiding the development of tailored immunotherapeutic strategies for HCC patients with different etiologies. In viral HCC, tumoral lesions tend to be more infiltrated by M0 macrophages, dendritic cells, and mast cells, along with the increased presence of naive B cells, plasma cells, follicular helper T cells, and regulatory T cells, whereas non-viral HCC tends to display a significantly higher infiltration rate of M2 macrophages [ 49 , 50 ]. Consistently with this, an in-depth in vitro study employing cytometry and next-generation sequencing compared the tumor microenvironment in patients with HBV-related HCC and those with non-viral HCC, revealing distinct immune signatures [ 51 ].…”
Section: Pathogenesis Of Masld-related Hcc and Tumor Microenvironmentmentioning
confidence: 99%
“…In yet another study, Zhang et al demonstrated that HBV-HCC, HCV-HCC and non-viral HCC had similar molecular phenotypes with inhibition of immune pathways. In the immune microenvironment associated with virus induced HCC there was, however, excessive M2-type macrophage polarization associated with immune suppression ( Zhang YZ. et al, 2022 ).…”
Section: Influence Of Liver Disease On the Hepatic Immune Microenviro...mentioning
confidence: 99%